Omental torsion - Jain Paresh; Chhabra Sheri; Parikh Ketan; Vaidya Amrish (Wolters Kluwer Medknow Publications, 2008)
Omental torsion is a rare cause of acute abdominal pain, and clinically mimics acute appendicitis. A 11-year-old boy presented with symptoms and signs suggestive of appendicitis. A computed tomography of abdomen revealed findings suggestive of omental torsion. Diagnostic laparoscopy confirmed the diagnosis of torsion of a segment of the greater omentum.